Socio Scientific Issues-Based Argumentation Assessment for Middle School Students - Irwanto Arsyim; Bibin Rubini; Indarini Dwi Pursitasari (Jurnal Penelitian Pendidikan IPA, 2022)
This research was conducted to produce an Argumentation Assessment based on Scientific Social Issues. This study uses the R&D method. This research is in the Develop stage, namely conducting expert validation and limited trials. The SSI-based argumentation instrument trial was conducted on 15 and 30 grade IX students of SMP Adik Irma Jakarta. Data collection techniques were carried out by written tests and assessment of argumentation test questions. The assessment of argumentation test questions is given to material experts and 10 teachers. The CVI test was conducted by ten teachers, in an average CVI score of 0.9 with a very appropriate category. The first trial was conducted with ten written tests, resulting in six assessments that were declared valid and reliable with a validity test value > 0.514 and a Cronbach's Alpha reliability test score > 0.514. Furthermore, the second trial was carried out on thirty students with five assessments, resulting in Validity Test scores > 0.361, Reliability Test scores > 0.361, and the developed assessment was able to measure students' argumentation skills at level three according to the Toulmin Analysis Pattern (TAP). The conclusion is that the assessment developed can be used by teachers to measure students' argumentation skills.